Influence of alumina content on the sinterability of the Cu-Al2O3 pseudo alloy (composite) - Anđić, Zoran (Materiali in tehnologije, 2004)
Mechanism and kinetics of the thermally activated processes of the occurring by annealing of cold pressed samples of Cu-Al2O3 powder. With electrical resistance measurements in non-isothermal and isothermal conditions and with microstructural analysis, the influence of Al2O3 and temperature on the sintering process of ?$Cusub(1-x)-Alsub2Osub3(x)$? powders was determined. By measuring the isothermal change of specific electrical resistance at temperatures below the recovering temperature (400-680 K), the kinetics parameters of the process are determined. The sintering was performed in hydrogen at the temperatures of (1073, 1173, 1273) K for (15, 30,60, 120) min. The results show that with incresing Al2O3 content the sintering time increases at all the examined temperatures.
Keywords: sintranje; aluminijev oksid; baker; električna upornost; mikrostruktura